Pelaksanaan Pendaftaran Tanah Sistematis Lengkap di Desa Menanga, Kecamatan Rendang, Kabupaten Karangasem - Nyoman Handytya Wiarsa Putra; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Preferensi Hukum, 2021)
Complete systematic land registration is a program organized by the government, specifically the "Ministry of Agrarian Affairs and Spatial Planning or Head of the National Land Agency". with the aim of increasing the number of land registrations issuing certificates in Indonesia. This is very important, so it is hoped that the participation of the whole community in the importance of certificates and it is hoped that the National Land Agency will provide socialization about the importance of ownership of land rights. Its application is contained in the Regulation of the Minister of Agrarian Affairs and Spatial Planning or the Head of the National Land Agency of the Republic of Indonesia Number 6 of 2018 concerning Complete Systematic Land Registration. This study aimed to examine the process of implementing a complete systematic land registration and its obstacles and to examine the efforts to implement a complete systematic land registration in the village of Menanga, Rendang District, Karangasem Regency. The method used was empirical legal research. Sources of data used were primary and secondary legal data, then analyzed through interpretation and qualitative techniques. The results showed that the Implementation of Complete Systematic Land Registration in Menanga Village, Rendang District, Karangasem Regency was carried out to achieve legal certainty of land rights ownership. The implementation of this program has not been effective and has not been implemented optimally due to the low participation in the management of land certificates.